Air pollution and climate response to aerosol direct radiative effects: A modeling study of decadal trends across the northern hemisphere. Issue 23 (14th December 2015) - Xing, Jia; Mathur, Rohit; Pleim, Jonathan; Hogrefe, Christian; Gan, Chuen‐Meei; Wong, David C.; Wei, Chao; Wang, Jiandong
Abstract: Decadal hemispheric Weather Research and Forecast‐Community Multiscale Air Quality simulations from 1990 to 2010 were conducted to examine the meteorology and air quality responses to the aerosol direct radiative effects. The model's performance for the simulation of hourly surface temperature, relative humidity, wind speed, and direction was evaluated through comparison with observations from NOAA's National Climatic Data Center Integrated Surface Data. The inclusion of aerosol direct radiative effects improves the model's ability to reproduce the trend in daytime temperature range which over the past two decades was increasing in eastern China but decreasing in eastern U.S. and Europe. Trends and spatial and diurnal variations of the surface‐level gaseous and particle concentrations to the aerosol direct effect were analyzed. The inclusion of aerosol direct radiative effects was found to increase the surface‐level concentrations of SO2, NO2, O3, SO4 2−, NO3 −, and particulate matter 2.5 in eastern China, eastern U.S., and Europe by 1.5–2.1%, 1–1.5%, 0.1–0.3%, 1.6–2.3%, 3.5–10.0%, and 2.2–3.2%, respectively, on average over the entire 21 year period. However, greater impacts are noted during polluted days with increases of 7.6–10.6%, 6.2–6.7%, 2.0–3.0%, 7.8–9.5%, 11.1–18.6%, and 7.2–10.1%, respectively. Due to the aerosol direct radiative effects, stabilizing of the atmosphere associated with reduced planetary boundary layer height and ventilation leads to an enhancement of pollution. Consequently, the continual increase of aerosol optical depth (AOD) in eastern China leads to an increasing trend in the air quality feedback which exacerbates air pollution, while emission reductions in eastern U.S. and Europe result in a declining trend in both AODs and feedback which make the air pollution control strategies more effective. Key Points: Strong diurnal variations are found in meteorology and air quality responses to aerosol direct effects Impacts from aerosol direct effects contributed to the observed historical trend in DayTR Aerosol direct radiative effects have an "enlarging effect" on surface‐level air pollution